Teacher Presence Application with Geolocation and Self Potrait using Android-based Prototype Method at MTsN Binjai - Gunawan, Aldi; Ikhwan, Ali (Sistemasi: Jurnal Sistem Informasi, 2024)
Technological advances are developing just like scientific advances. One example of the latest technological advances is the online attendance system. At MTsN Binjai, attendance currently uses electronic-based technology, namely fingerprints, but still has several weaknesses. For example, the device cannot be used when the electricity fails, and the attendance process must be carried out alternately due to dependence on one device. In addition, fingerprints only record attendance, do not facilitate the submission of permits or illnesses, so the admin must do double work. The thing that was researched was the use of descriptive methods and the development of a system with the prototype method. The purpose of this study is to generate an Android-based absence application that can be accessed through the personal cellphones of teachers and staff who can facilitate attendance and submission of sick permits. The results of the study are expected to be a reference for schools to improve discipline for attendance.